The Research on the Ho Chi Minh City University of Technology and Education Students’ Choice of Ethical Values - Le , Thị Vân Anh (Journal of Technical Education Science, 2018)
Once the social activists are still alive and developing, as well as instability, loss, and conflicts still occur, then morality, values, ethical values ​​will always be the important problem mentioned and interested in studying whether in any country or in any era. Thus, this study was conducted for two purposes as follow (1) It provides the readers with an overview of the students’ ethical values at Ho Chi Minh City University of Technology and Education at present; (2) and the relationship between sex, religion, training time and the students’ choice of ethical values. The questionnaire is used to determine the students’ ethical values at Ho Chi Minh City University of Technology and Education; The measure of observing daily attitudes and behaviors is taken; The interviews are also given to confirm the results from the survey.The results of the study show that the students are highly conscious and have a set of standards and knowledge base suitable for their selection of ethical values, but they still don’t pay much attention to some of the inner ethical values. Also, there is no difference between sex, religion, training time and the students’ ethical value choice